An Agent-Based Model for Normative Hierarchical Organizations considering Goal Decomposition Process - Freire, Emmanuel S. S.; R. Jr, Robert M.; Cortés, Mariela I.; Campos, Gustavo A. L. (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2018)
The ideas about the structures and interactions that happen in human organizations have been used to model agent-based normative hierarchical organizations. Some works have used social control to regulate the agents’ behavior to achieve an organizational goal, i.e., that is decomposed in a set of meaningful sub goals to the agents. Many organizational models have been defined to model these organizations, but they do not relate, more specifically, the agents in the hierarchical structure with the sub goals resulting from the decomposition process. This paper proposes an approach to bridge this gap, i.e., to model agent-based normative hierarchical organizations along with the goal decomposition process. In short, we extended a model found in Literature considering the goal decomposition defined in Moise+. We used UML diagrams to illustrate our extension.